Features and Functionalities of Medical Mobile Applications for the Endemic Phase of COVID‐19: Review and Content Analysis - Loy, Mei Jun; Goh, Khang Wen; Norliza, Osili; Long, Chiau Ming *; Dhaliwal, Jagjit Singh; Hermansyah, Andi; Al-Worafi, Yaser Mohammed; Lee, Kah Seng (HH Publisher, 2022)
The study's objective was to assess the features and content of the COVID-19 mobile applications accessible in the Apple AppStore. A content analysis, comparison, and functionality evaluation of a few COVID-19 related mobile applications was performed. The search for COVID -19 related apps in the iOS AppStore took place between February 1 and March 31, 2022. The mobile applications received a maximum of 7 points (basic feature assessment) and 8 points overall (functionality assessment). The requirements were fully met by receiving one point. Frequencies from descriptive statistics were used to allude to the applications' features according to the app's basic purpose. A total of 234 applications were recognized using the keywords to exploreCOVID-19 related mobile applications in Apple AppStore. However, 58 mobile applications (24.8%) relevant to COVID-19 were evaluated. According to the findings of an evaluation of basic aspects of mobile applications, 89.7% require an internet connection, 70.7% have a size of less than 50 MB, 96.6% require no funding, 58.6% include educational content, and 60.3% offer advice from the applications. In terms of score, 41.4% scored three or below, whereas 58.6% scored four or above. Functionality assessment wise, 79.3% included information regarding COVID-19, 12.1% included COVID-19 contact tracing, 17.2% had vaccination status, a health authority maintained 50%, 31.0% included COVID-19 statistics, and 25.8% were able to report ART/PCR test. In terms of score, 91.4% scored three points or less, and 8.6% scored four points or more. This study has discovered several applications that could effectively prevent COVID-19 pandemic spread. Based on the findings, mobile applications that would be recommended are the ones supported by the government health administration of the respective country. App development companies’ applications show that competent healthcare personnel was not involved in developing the applications. Online consultation with healthcare professionals might help the public who do not have access to the nearest hospital.